Moral education and the justification of basic moral standards: Replies to Clayton, Stevens and D'Olimpio. Issue 4 (2nd October 2019) - Hand, Michael
ABSTRACT: Matthew Clayton, David Stevens and Laura D'Olimpio have advanced a series of objections to arguments I set out in my recent book A Theory of Moral Education – in particular to the problem-of-sociality justification for basic moral standards. Here I reply to their objections.